2014
DOI: 10.1039/c3cc46903d
|View full text |Cite
|
Sign up to set email alerts
|

High mitochondrial accumulation of new gadolinium(iii) agents within tumour cells

Abstract: The first bifunctional Gd(III) complexes covalently bound to arylphosphonium cations and the first tumour-cell selective mitochondrial agents designed for potential application in binary cancer therapies are reported. The highest in vitro cellular uptake for any Gd complex reported to date is described, with levels exceeding 10(10) Gd atoms per tumour cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 20 publications
5
63
1
Order By: Relevance
“…By means of synchrotron X‐ray fluorescence (XRF) quantification, it was demonstrated that that these complexes were able to accumulate Gd at high levels (ca. 10 11 Gd atoms per tumour cell), a few orders of magnitude higher than therapeutically relevant thresholds 12…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…By means of synchrotron X‐ray fluorescence (XRF) quantification, it was demonstrated that that these complexes were able to accumulate Gd at high levels (ca. 10 11 Gd atoms per tumour cell), a few orders of magnitude higher than therapeutically relevant thresholds 12…”
Section: Introductionmentioning
confidence: 97%
“…A new avenue for the design of Gd‐agents for use in binary therapies includes mitochondrially‐targeted agents 12. Delocalised lipophilic cations (DLCs) have garnered increasing attention for their ability to act as tumour‐targeted delivery vectors for a range of tumour imaging and therapeutic applications 13.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four structurally related phosphonium ligands L1 to L4 containing a phosphonium center, a xylyl linker and the macrocycle DO3A (1,4,7,10‐tetraazacyclododecane,‐ N,N ′ ,N ″‐triacetic acid) were synthesized according to Scheme and purified using reversed‐phase high‐pressure liquid chromatography (HPLC) on a C18 column. The “cold” Ga complexes were synthesized in high purity by addition of GaCl 3 to ligands L1 to L4 in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our research group has investigated similar Gd(III) phosphonium salts as potential tumor mitochondrial targeting agents for neutron capture and photon activation therapies . In vitro studies of these compounds confirmed their modest toxicity (IC 50 > 1 mM), high uptake by T98G human glioblastoma cells (>1500 ng Gd/mg protein), and high selectivity of tumor to normal cells compared with the control noncancerous SVGp12 fetal glial cell line.…”
Section: Introductionmentioning
confidence: 99%